Decay factor characterisation of selected paper products under optimal landfill anaerobic conditions using bench- and pilot-scale reactors - Jabaar, Thaakira (Stellenbosch : Stellenbosch University, 2025)
Jabaar, T. 2025. Decay factor characterisation of selected paper products under optimal landfill anaerobic conditions using bench- and pilot-scale reactors. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0931f804-178f-45a9-956f-7ccdadc220c3